PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT, PERFORMANCE APPRAISAL SYSTEM, DAN IT CAPABILITY TERHADAP KINERJA KARYAWAN DIVISI OFFICE PT INDOMARCO ADI PRIMA SURABAYA - Muhammad Ilham Habib Akbar; Tri Andjarwati (CV. ADIBA AISHA AMIRA, 2026)
This study looks at how Perceived Organizational Support, Performance Appraisal System, and IT Capability affect employee performance in the Office Division of PT Indomarco Adi Prima Surabaya. It checks how each factor affects performance on its own and together. The research uses numbers and surveys to collect data from 60 employees in the Office Division, since there are not many employees to sample. The data is analyzed using multiple linear regression with SPSS version 26, along with tests to make sure the data is reliable and accurate. The results show that all three factors have a big influence on how well employees perform. This means that if a company improves support from the organization, uses a fair and clear performance system, and has good IT tools, it can help employees work better. The study also gives suggestions for company leaders to create a better plan that combines HR and technology management.